Analysis of the Readiness of Driving School Teachers in Implementing the Independent Curriculum at the PAUD Level in Situbondo Regency - Rakhman, Fathor; Surur, Miftahus (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
This research analyzes PAUD teachers in Situbondo as driving school teachers in adopting and implementing the Independent Curriculum. The results of this research provide an in-depth understanding of how teachers understand the curriculum concept, the school's efforts to integrate it, management based on the Independent Curriculum. This research used qualitative methods using in-depth interviews and observations of 41 teachers from various kindergartens in Situbondo, including Nurul Anshor Islamic Kindergarten, DWP 1 Besuki Kindergarten, DWP 1 Asembagus Kindergarten, Kartika IV-71 Kindergarten, Nurul Huda Kindergarten, DWP 1 Jatibanteng Kindergarten. , and Hasyim Asy'ari Kindergarten. The research results show that the majority of PAUD teachers in Situbondo have a basic understanding of the Merdeka Curriculum, although there are variations in their level of understanding. This emphasizes the need for additional training to ensure teachers can implement it effectively. Kindergarten schools in Situbondo have demonstrated a strong commitment to integrating the Merdeka Curriculum into children's learning experiences. Collaboration between teachers and school staff is a key factor in school operational management. School management has also adopted the principles of the Independent Curriculum in school management and development. Overall, these findings contribute to important insights into the role of PAUD teachers as drivers in creating an educational environment in accordance with the principles of the Independent Curriculum. All the results of this research can serve as guidance for related parties in efforts to improve the quality of PAUD in Situbondo.